GREEN MINDS, FUTURE TEACHERS: EXPLORING ENGLISH PRESERVICE TEACHERS’ PERCEPTIONS ON GREEN EDUCATION - Nurkhamidah, Neni (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Green education for students is an effective strategy for reducing environmental damage. However, its implementation faces various challenges, including insufficient teacher knowledge. This research aims to explore teachers' perceptions of the implementation of green education. Six preservice teachers from the English Department of MNC University participated in the study. A purposive sampling technique was used to select the participants. The study adopted a descriptive method with a qualitative approach, employing interviews to gather data. The findings show that preservice teachers in the English Education program at MNC University possess both the knowledge and a favorable perception of green education in schools. It is suggested that all stakeholders support the implementation of green education in Indonesia. By involving all parties, from educators to policymakers, the program can be more effective and impactful.